Letter from Carl D. Duncan to Patricia Whiting, January, 1966 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Duncan thanks Whiting for her companionship and admires a friend of Whiting's whom he feels represents the thoughts of the new generation.